Dietary patterns associated with body mass index (BMI) and lifestyle in Mexican adolescents - Laura Elisa Gutiérrez-Pliego; Eneida del Socorro Camarillo-Romero; Laura Patricia Montenegro-Morales; José de Jesus Garduño-García (BMC, 2016)
Abstract Background The objetive in this study is to determine the relationship between dietary patterns, BMI, type 2 diabetes mellitus family history (T2DMFH) and some lifestyle variables such as smoking and skipping breakfast in a Mexican adolescent population. Methods Cross-sectional, observational, analytical study.Subjetcts: 14-16 years old male and female adolescents (n 373). A previously validated food frequency questionnaire (FFQ) was used and dietary patterns were derived using principal component analysis (PCA). Scores for dietary patterns were categorized by tertiles. Results Three major dietary patterns that explained 47 % of variance were found: westernized, high in protein/fat and prudent pattern. Subjects at the highest tertile of prudent pattern had lower BMI. And was also associated with less T2DMFH and less smoking habit when compared with the lowest tertile. We found a positive correlation between BMI and high scores for westernized and high in protein/fat pattern Conclusions Dietary patterns of adolescents are a public health concern because there is a direct association between inadequate diet at this early age and obesity